ANALISA POTENSI UNTUK PENGEMBANGAN INDUSTRI KULIT DI GUNUNG PUNTANG KABUPATEN BANDUNG - Dian Kurnianingrum; Iston Dwija Utama; Nur Azmi Karim; Chyntia Ika Ratnapuri (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2019)
Gunung Puntang in Bandung Regency West Java is known as one of a coffee and vegetable producer. Moreover, it is also wellknown as a leather craft industry center in West Java. Research entitled "Potential Analysis to Development Leather Industry in Gunung Puntang, Bandung Regency" is an initial research that will become a basis for further research. Short-term goal of this research is to figure out the leather industry potential in villages which located in Mount Puntang. So in the future, researchers could develop effective strategies for those areas. This research use external and internal factors analysis to conclude the opportunities, threaths, strengths and weaknesses of the industry, in order to solve the research questions. As a long-term goal, it hopes that this research result could increase village GDP and achieve community welfare.